Active compounds of fingerroot (Boesenbergia pandurata) for obesity treatment: in silico approaches - Yuniarto, Ari; Aji, Abdul; Ramadhani, Anggia Noor; Permatasari, Galuh Wening (Fakultas Farmasi, Universitas Surabaya, 2022)
Obesity has become increasingly prevalent worldwide each year. Several studies have proven that herbs are effective in preventing obesity. The research delved into the active compounds of Boesenbergia pandurata to reveal their mechanisms of action by utilizing bioinformatics approaches. The research methods included active compounds selection, QSAR analysis, networking analysis, molecular docking, and ADME prediction. The QSAR analysis predicted that the active compounds were correlated with some theoretical activities with more than 0.5 probability, namely vasoprotective, anti-hypercholesterolemic, anti-inflammatory, free radical scavenging, and as a lipid metabolism regulator and TNF expression inhibitor. Furthermore, the results of the networking analysis showed that five compounds (pinocembrin, cardamonin, flavokawain B, flavokawain C, and tectochrysin) had direct interactions with RPS6KB1. Pinocembrin exhibited the highest binding affinityof -7.26 kcal/mol, although not as strong as that of the control ligand (FS9). The ADME prediction indicated that the five compounds were non-toxic and had excellent absorption. It can be concluded that the active compounds of B. pandurata have the ability to improve metabolic syndrome, especially obesity, in silico through several mechanisms, such as suppression of pro-inflammatory cytokine, regulation of lipid metabolism, and those associated with antioxidants.